Hydrogel carbohydrate-electrolyte beverage does not improve glucose availability, substrate oxidation, gastrointestinal symptoms or exercise performance, compared with a concentration and nutrient-matched placebo - McCubbin, A. J.; Zhu, A.; Gaskell, S. K.; Costa, R. J. S. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
The impact of a carbohydrate-electrolyte solution with sodium alginate and pectin for hydrogel formation (CES-HGel), was compared to a standard CES with otherwise matched ingredients (CES-Std), for blood glucose, substrate oxidation, gastrointestinal symptoms (GIS; nausea, belching, bloating, pain, regurgitation, flatulence, urge to defecate, and diarrhea), and exercise performance. Nine trained male endurance runners completed 3 hr of steady-state running (SS) at 60% VO2max, consuming 90 g/hr of carbohydrate from CES-HGel or CES-Std (53 g/hr maltodextrin, 37 g/hr fructose, 16% w/v solution) in a randomized crossover design, followed by an incremental time to exhaustion (TTE) test. Blood glucose and substrate oxidation were measured every 30 min during SS and oxidation throughout TTE. Breath hydrogen (H2) was measured every 30 min during exercise and every 15 min for 2 hr postexercise. GIS were recorded every 15 min throughout SS, immediately after and every 15-min post-TTE. No differences in blood glucose (incremental area under the curve [mean ± SD]: CES-HGel 1,100 ± 96 mmol·L-1·150 min-1 and CES-Std 1,076 ± 58 mmol·L-1·150 min-1; p = .266) were observed during SS. There were no differences in substrate oxidation during SS (carbohydrate: p = .650; fat: p = .765) or TTE (carbohydrate: p = .466; fat: p = .633) and no effect of trial on GIS incidence (100% in both trials) or severity (summative rating score: CES-HGel 29.1 ± 32.6 and CES-Std 34.8 ± 34.8; p = .262). Breath hydrogen was not different between trials (p = .347), nor was TTE performance (CES-HGel 722 ± 182 s and CES-Std: 756 ± 187 s; p = .08). In conclusion, sodium alginate and pectin added to a CES consumed during endurance running does not alter the blood glucose responses, carbohydrate malabsorption, substrate oxidation, GIS, or TTE beyond those of a CES with otherwise matched ingredients.